A consistent bottom-up approach for deriving a conceptual framework for public sector financial accounting. Issue 6 (18th August 2021) - Oulasvirta, Lasse
ABSTRACT: Discussion to date has focused on whether business-style accrual accounting fits the public sector, rather than analysing which alternative options of accrual accounting best serve the needs of public sector stakeholders. This paper looks at what the primary users of government accounting information actually need and describes a new analytical approach that can be used to assess the existing public sector financial accounting standards. The author then presents the most suitable conceptual framework for the public sector. The paper argues that the income statement first approach is better than the balance sheet approach for the public sector.